The Determining Role of Mitochondrial Reactive Oxygen Species Generation and Monoamine Oxidase Activity in Doxorubicin-Induced Cardiotoxicity - Antonucci, Salvatore; Di Sante, Moises; Tonolo, Federica; Pontarollo, Laura; Scalcon, Valeria; Alanova, Petra; Menabò, Roberta; Carpi, Andrea; Bindoli, Alberto; Rigobello, Maria Pia; Giorgio, Marco; Kaludercic, Nina; et al. (Antioxidants & redox signaling, 2021)
Aims: Doxorubicin cardiomyopathy is a lethal pathology characterized by oxidative stress, mitochondrial dysfunction, and contractile impairment, leading to cell death. Although extensive research has been done to understand the pathophysiology of doxorubicin cardiomyopathy, no effective treatments are available. We investigated whether monoamine oxidases (MAOs) could be involved in doxorubicin-derived oxidative stress, and in the consequent mitochondrial, cardiomyocyte, and cardiac dysfunction. Results: We used neonatal rat ventricular myocytes (NRVMs) and adult mouse ventricular myocytes (AMVMs). Doxorubicin alone (i.e., 0.5 μM doxorubicin) or in combination with H2O2 induced an increase in mitochondrial formation of reactive oxygen species (ROS), which was prevented by the pharmacological inhibition of MAOs in both NRVMs and AMVMs. The pharmacological approach was supported by the genetic ablation of MAO-A in NRVMs. In addition, doxorubicin-derived ROS caused lipid peroxidation and alterations in mitochondrial function (i.e., mitochondrial membrane potential, permeability transition, redox potential), mitochondrial morphology (i.e., mitochondrial distribution and perimeter), sarcomere organization, intracellular [Ca2+] homeostasis, and eventually cell death. All these dysfunctions were abolished by MAO inhibition. Of note, in vivo MAO inhibition prevented chamber dilation and cardiac dysfunction in doxorubicin-treated mice. Innovation and Conclusion: This study demonstrates that the severe oxidative stress induced by doxorubicin requires the involvement of MAOs, which modulate mitochondrial ROS generation. MAO inhibition provides evidence that mitochondrial ROS formation is causally linked to all disorders caused by doxorubicin in vitro and in vivo. Based upon these results, MAO inhibition represents a novel therapeutic approach for doxorubicin cardiomyopathy.
Keywords: Monoamine Oxidase; Animals; Doxorubicin; Heart Ventricles; oxidační stres; reactive oxygen species (ROS); Mitochondria; Myocytes, Cardiac; srdeční komory; Oxidative Stress; Mice; Reactive Oxygen Species; monoamine oxidase; mitochondria; myši; monoaminoxidasa; mitochondrie; cardiomyopathy; doxorubicin; reaktivní formy kyslíku; krysa rodu Rattus; zvířata; Rats; kardiomyocyty